Parametric optimization and control for a smart Proton Exchange Membrane Water Electrolysis (PEMWE) system. (July 2020) - Ogumerem, Gerald S.; Pistikopoulos, Efstratios N.
Abstract: Hydrogen production from Proton Exchange Membrane Water Electrolysis (PEMWE) system is attracting attention due to its ability to circumvent the effect of the intermittent nature of variable renewal energy. However, the relatively high operating temperatures of the PEMWE system exacerbates the degradation of polymer membranes in PEMWE system. This paper describes the development of an optimal thermal management strategy for a PEMWE system that can attenuate the long-term effects of high operating temperatures or rapid temperature changes on the polymer membranes. The thermal management strategy is tested on a laboratory scale smart PEMWE system. First, a high fidelity mathematical model of the smart PEMWE is developed and validated based on which the application of the PARameteric Optimization and Control (PAROC) framework results in the design of an explicit model predictive controller which is deployed into the laboratory PEMWE system. It is shown that the smart PEMWE prototype system empowered with the embedded control policy achieves effective temperature control across the electrolyzer maintaining the integrity of the membrane electrode assembly. Highlights: Proposed an optimal operating strategy to mitigate membrane degradation. Developed an explicit Model Predictive Controller (eMPC) using the PAROC Framework. Designed and built a lab-scale PEM Water Electrolysis (PEMWE) prototype. Demonstrated the implementation of the eMPC on the PEMWE prototype.